Distinct effects of cognitive versus somatic anxiety on cognitive performance in old age: the role of working memory capacity. (2nd April 2020) - Mella, Nathalie; Vallet, Fanny; Beaudoin, Marine; Fagot, Delphine; Baeriswyl, Marie; Ballhausen, Nicola; Métral, Grégoire; Sauter, Julia; Ihle, Andreas; Gabriel, Rainer; Oris, Michel; Kliegel, Matthias; et al.
Abstract: Objective: The adverse effects of anxiety on cognition are widely recognized. According to Attentional Control Theory, worry (i.e. facet of cognitive anxiety) is the component that is responsible for these effects, and working memory capacity (WMC) plays an important role in regulating them. Despite the increasing importance of this problem with aging, little is known about how these mechanisms interact in old age. In this study, we explored the distinct contributions of the somatic and cognitive components of anxiety to neuropsychological performance, and the potential moderating role of WMC. Method: We administered cognitive tasks testing processing speed, cognitive flexibility and working memory to 605 older adults, who also underwent depression and test anxiety assessments (data from VLV study). Results: Multiple regression analyses showed that cognitive (but not somatic) aspects of anxiety affected cognitive flexibility. The effect of cognitive anxiety on processing speed was moderated by WMC: the anxiety-performance association was lower for participants with greater WMC. Conclusion: Results confirmed the specific role of worry in the anxiety–performance relationship in old age and supported the hypothesis that working memory resources regulates its deleterious effect on cognition. The absence of a moderation effect in the more costly switching task may reflect a limitation of resources with aging.